Jonibek Sultan - The First Governor of Shaibani of Ferghana Valley - Lolaxon Teshebaeva (Genius Journals, 2023)
The article discusses the first governor of Shaibani in the Fergana Valley based on historical sources and literature
Keywords: Fergana Valley; Sheibaniykhan; Janibek Sultan